2019
DOI: 10.3389/fncel.2019.00538
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inflammation and Unchanged Density of Synaptic Vesicle Glycoprotein 2A (SV2A) in the Postmortem Frontal Cortex of Alzheimer’s Disease Patients

Abstract: Sections from the middle frontal gyrus (Brodmann area 46) of autopsy-confirmed Alzheimer's disease (AD) patients and non-demented subjects were examined for the prevalence of hallmark AD pathology, including amyloid-β (Aβ) plaques, phosphorylated tau (pTau) tangles, neuroinflammation and synaptic loss (n = 7 subjects/group). Dense-core deposits of Aβ were present in all AD patients (7/7) and some nondemented subjects (3/7), as evidenced by 6E10 immunohistochemistry. Levels of Aβ immunoreactivity were higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
(42 reference statements)
6
26
0
Order By: Relevance
“…We also show that increases in tau are broadly associated with decreases in ODI and NDI and increases in fISO. Our findings are supported by recent postmortem PET evidence showing a negative relationship between tau and synaptic density PET and a positive relationship between tau and neuroinflammation-related PET in the middle frontal gyrus (Brodmann area 46) of AD patient tissue 56 . While tau aggregation reflects AD’s direct etiology, fISO likely captures downstream neuroinflammatory processes, which are useful measures of cognitive decline in their own right and can supplement tau PET imaging.…”
Section: Discussionsupporting
confidence: 88%
“…We also show that increases in tau are broadly associated with decreases in ODI and NDI and increases in fISO. Our findings are supported by recent postmortem PET evidence showing a negative relationship between tau and synaptic density PET and a positive relationship between tau and neuroinflammation-related PET in the middle frontal gyrus (Brodmann area 46) of AD patient tissue 56 . While tau aggregation reflects AD’s direct etiology, fISO likely captures downstream neuroinflammatory processes, which are useful measures of cognitive decline in their own right and can supplement tau PET imaging.…”
Section: Discussionsupporting
confidence: 88%
“…To understand the biphasic relationship between tau accumulation and synaptic density, one must consider other key players in synaptotoxicity in tauopathies, such as neuroinflammation 47 . Recent in vivo studies have confirmed the regional co-localisation of inflammation and [ 18 F]AV-1451 binding in PSP 48 , in line with previous in vivo 49,50 , and post mortem 51 reports of the tight interplay between neuroinflammation and tau accumulation in tauopathies. There is growing evidence that these two pathological processes affect synaptic function both independently and synergistically 40,42 .…”
Section: Discussionsupporting
confidence: 83%
“…Under normal physiological conditions, TSPO expression is low in brain glial cells but is significantly increased in brain injury and inflammation, a feature that makes it particularly suitable for assessing active glial cells (Biswas et al, 2018 ; Werry et al, 2019 ). Significant increases in TSPO expression were found in many neurodegenerative diseases, such as Alzheimer’s disease (AD; Metaxas et al, 2019 ), Parkinson’s disease (PD; Gerhard, 2016 ), and Huntington’s disease (HD; Metaxas et al, 2019 ). However, the causal relationship between changes in TSPO protein expression and the occurrence of neurodegenerative diseases is still unclear.…”
Section: Introductionmentioning
confidence: 99%